Using thermal analysis techniques for identifying the flash point temperatures of some lubricant and base oils - Aksam Abdelkhalik; Hany Elsayed; Mohamed Hassan; Mohamed Nour; A.B. Shehata; Maher Helmy (Egyptian Journal of Petroleum)
The flash point (FP) temperatures of some lubricant and base oils were measured according to ASTM D92 and ASTM D93. In addition, the thermal stability of the oils was studied using differential scanning calorimeter (DSC) and thermogravimetric analysis (TGA) under nitrogen atmosphere. The DSC results showed that the FP temperatures, for each oil, were found during the first decomposition step and the temperature at the peak of the first decomposition step was usually higher than FP temperatures. The TGA results indicated that the temperature at which 17.5% weigh loss take placed (T17.5%) was nearly identical with the FP temperature (±10 °C) that was measured according to ASTM D92. The deviation percentage between FP and T17.5% was in the range from −0.8% to 3.6%. Keywords: Flash point, TGA, DSC